Pengkayaan Besi (Fe) dan Seng (Zn) dalam Beras dan Karakter Penentu Varietas Padi Sawah Efisien pada Tanah Vertisol dan Inseptisol - YUSTISIA, YUSTISIA; TOHARI, TOHARI; SHIDDIEQ, DJA’FAR; G, SUBOWO (Agrotrop : Journal on Agriculture Science; Vol 2 No 1 (2012))
Increasing concentration of Fe and Zn micronutrients in rice grain is needed to reduce a wide gap between micronutrients concentration in rice grain and daily recommended consumption, and to antisipate of rice consumption decreased consequence. The Fe and Zn micronutrients in rice grain is influenced by genetic, soil type and management fertilizer factors. The major of rice field and intensively lowland rice production in Indonesia is conducted in Inceptisols and the others is conducted in Vertisols. This research conducted to identify rice genotypes based on their Fe and Zn concentrations in whole brown rice and to identify specific characters of efficient genotypes based on their potentially increasing concentrations of Fe and Zn in whole brown rice. The experiment was conducted in the Greenhouse of Agriculture Faculty, Gadjah Mada University during Dry Season 2008. The experiment was arranged using Randomized Complete Block Design with three replications. Two different soils (Vertisols and Inceptisols) as a first factor, and genotypes (Cimelati, Pandan Wangi, Ciherang, Cisokan, Widas dan IR 64) as a second factor. Fertilizer application in Inceptisols was applied at the rate of 222, 26 kg ha-1 N, 56,80 kg ha-1 P2O5 and 47,67 kg ha-1 K2O. In Vertisols, fertilizer was applied at the rate of 136,38; 52,29 and 43,88 kg ha-1 N, P2O5 and K2O respectively. The result revealed that the concentrations of Fe and Zn in whole brown rice of Widas and Ciherang genotypes in Inceptisols was higher than that it is in Vertisols. The Fe and Zn concentrations in whole brown rice of Widas were 19,8 ppm and 24,43 ppm and Ciherang were 11,40 ppm and 24,55 ppm respectively. The Widas and Ciherang are the efficient genotypes and Cimelati is the inefficient genotype. The efficient genotypes had darker leaves, narrower leaves, lower yield decrease, higher grain yield efficiency index, compared to the inefficient genotypes. The maximal yield decreased for selecting efficient rice genotypes with NPK fertilizer at the 222, 26 kg ha-1 N, 56,80 kg ha-1 P2O5 and 47,67 kg ha-1 K2O compared to the without NPK fertilizer obtained of arround 41,49%.